2020
DOI: 10.3390/molecules25184292
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Suppresses Cross-Talk between Colorectal Cancer Cells and Stromal Cells in Multicellular Tumor Microenvironment: A Bridge between In Vitro and In Vivo Tumor Microenvironment Study

Abstract: The interaction between tumor cells and the tumor microenvironment (TME) is an important process for the development of tumor malignancy. Modulation of paracrine cross-talk could be a promising strategy for tumor control within the TME. The exact mechanisms of multi-targeted compound resveratrol are not yet fully understood. Whether resveratrol can modulate paracrine signal transduction-induced malignancy in the multicellular-TME of colorectal cancer cells (CRC) was investigated. An in vitro model with 3D-algi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 87 publications
1
40
0
Order By: Relevance
“…To address the role of Calebin A in modulating NF-κB attachment on DNA, we performed a DNA-binding assay with dithiothreitol (DTT) as earlier detailed (Buhrmann et al, 2020a). TME cultures were established and then nuclei and cytoplasm were separated from each other, from CRC cells that remained untreated and/or treated with Calebin A (1, 2, and 5 µM) plus DTT (5 mM) alone or in both for 1 h, as has been thoroughly outlined in previous work (Buhrmann et al, 2020a;Buhrmann et al, 2020b;Buhrmann et al, 2020c). The nuclei were then prepared, separated by SDS-PAGE and blotted as indicated earlier.…”
Section: Dna-binding Assaymentioning
confidence: 99%
“…To address the role of Calebin A in modulating NF-κB attachment on DNA, we performed a DNA-binding assay with dithiothreitol (DTT) as earlier detailed (Buhrmann et al, 2020a). TME cultures were established and then nuclei and cytoplasm were separated from each other, from CRC cells that remained untreated and/or treated with Calebin A (1, 2, and 5 µM) plus DTT (5 mM) alone or in both for 1 h, as has been thoroughly outlined in previous work (Buhrmann et al, 2020a;Buhrmann et al, 2020b;Buhrmann et al, 2020c). The nuclei were then prepared, separated by SDS-PAGE and blotted as indicated earlier.…”
Section: Dna-binding Assaymentioning
confidence: 99%
“…Its modulatory effects on inflammatory processes and related diseases, including OA and RA, have also been studied. In previous studies, our group has demonstrated the anabolic and protective effects of curcumin on IL-1β-, TNF-α-, or TNF-β-stimulated chondrocytes, indicating its chondroprotective properties for the treatment of OA and related osteoarticular problems [ 22 , 23 , 24 ]. Thus, NF-kB signaling participates in the pathogenesis of OA, has been identified as one of the most important signaling pathways, and significantly regulates OA-associated inflammatory mediators [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, over 50% of patients show resistance to 5-FU in the therapeutic course (15). RES has been found to inactive the NF-kB signaling pathway potently in earlier researches (104)(105)(106). The NF-kB signaling pathway not only closely links to inflammation and cancer (107), but also propels the process of EMT and metastasis (17).…”
Section: Colorectal Cancermentioning
confidence: 99%